Exercise Induced Bronchoconstriction - An Overview - Černohorská, Alicja; Bednarczyk, Daria; Białeta, Julia; Garbarczyk, Wiktor; Jurkiewicz, Michalina; Kapla, Albert; Napieralska, Agnieszka; Rowińska, Katarzyna; Pysiewicz, Wiktoria; Siembab, Karolina (Quality in Sport, 2025)
Exercise-induced bronchoconstriction (EIB) is a common condition among athletes, particularly those involved in endurance sports, and can significantly impact their performance and quality of life. The underlying mechanisms of EIB remain complex and are influenced by various factors, including airway cooling, dehydration, increased exposure to allergens and pollutants, and intense physical exertion. The inflammatory responses in the airways of athletes with asthma are often unique, with increased airway sensitivity and reactivity. Factors such as increased ventilation, pollutants, allergens, and airway remodeling contribute to the high incidence of EIB in athletes. The diagnosis of asthma and EIB relies on clinical symptoms, peak expiratory flow measurements, and bronchoprovocation tests, including exercise challenge testing and methacholine challenges. These methods help establish airway hyperresponsiveness and assess the severity of bronchoconstriction. Diagnosis can be complicated by the need for multiple tests, as symptoms and airway responsiveness may fluctuate with training intensity. Treatment and management strategies for EIB in athletes are multifaceted and include both pharmacological and non-pharmacological approaches. Non-pharmacological strategies emphasize asthma education, environmental control, and exercise modification. Pharmacological interventions commonly include inhaled glucocorticoids, β2-agonists, leukotriene modifiers, and mast cell stabilizers. These treatments aim to manage symptoms, improve lung function, and reduce the occurrence of bronchoconstriction. Successful management requires a coordinated approach, involving healthcare providers, sports medicine professionals, and coaches, to ensure proper diagnosis, treatment adherence, and the continued participation of athletes in their chosen sports.